MATIC IMPLICATIONS OF SUNDANESE PUPUH SONG IN BUILDING MORAL VALUES TOWARD ELEMENTARY SCHOOL STUDENTS - Solihin Ichas Hamid; Tuti Istianti (International Journal of Social Science, 2021)
The title above has explained the purpose of this study, which is observing Matic's implication of children's moral values acquisition from learning activities to sing Pupuh Sunda Song in Elementary Schools – West Java. The methodology used is ethno-pedagogic because the extent of data collection and exploration were conducted toward the concept containing values that existed and lived amid the society within the context of ethnic tradition, that is, as far as signs and meanings are stored and expressed in vocal art expressions in the form of Pupuh Sunda song acted as a medium is message education praxis. Therefore, the phenomenology approach was carried out to observe a series of phenomena that can be analyzed during the concept values repeated into the performer's subconscious, the song, movements, and expressions in shared or personal situations. The stressing keyword point in this study is the repetition that can be assumed as a mechanical act on every subject learn to sing moral message content sung. The mechanical process activities result by repeating song memorization, expressing moral values inside the song. Qualitatively, it can be described as an automatic implication that has the potential and function as a fostering for the concept of value in building the expected character. Such as the direct utterance stored in the song containing the invitation and teaching always to be cheerful, accept everything with generosity, care to all being (compassionate), diligent in studying and fond of working, respecting the parents and teachers, love to the homeland and defending the state and nations, which becomes the focus of study.